Long-term Survival in a Case of Renal Cell Carcinoma With Brain Metastases: A Case Report - Pooleri, Ginil Kumar (Clin Med Insights Case Rep, 2019)
Renal cell carcinoma with brain metastases is considered to have a poor prognosis. We are reporting a case of a 63-year-old male who showed excellent long term remission with a combination treatment of radiation and tyrosine kinase inhibitor for a solitary lesion in the brain, secondary to the renal tumor.